Man and Culture as Ontological Root of Technology Adoption for African Development - Surakat, Ajibola Moruph (NIU Journal of Humanities; Vol 6 No 1 (2021): KIU Journal of Humanities, Vol. 6 No. 1, March 2021, 2021)
Advancement in the technological pursuits of man has really helped in pushing back the frontier of ignorance and enhancing deeper mastery of man's environment. There is a pushing down of those barriers that hitherto dogged human's socio-economic existence. A fundamental thrust of this paper shows that man and cultural experience cannot be ruled out of those cacophonies of factors that could shape the development of a nation. Ontologically, this paper opines that a sound philosophy of technological development must take root from the situation and cultural experience of the people, inextricably connecting both together. Therefore, the paper examines the ontological interpretation of man in Africa with emphasis drawn from Yoruba theory of human nature. This is pitched against the vibrant culture of development. The implication of a technicistic view of development is stated vis-a-vis the nature of man. The paper posits that African culture must be the primal point in the search of answers to the problem of development in the continent; this can then be harmonized with the global trend on terms defined by the people's situation and continuation Keywords: Ontology, Technology, Science, Culture , Development.